PENERAPAN PRIVATE CLOUD STORAGE SEBAGAI MEDIA SHARING DAN BACKUP DATA DI PT. TELKOM INDONESIA KANDATEL KISARAN - Dede Hernowo; Rr Yuliana Rachmawati K; Uning Lestari (Jurnal Jarkom, 2016)
Inside the world of work there are many difficulties that hinder the activities in the work, one of them is when the data sharing. They needed an application as a place or media to share information and data on a single company. Cloud storage is a solution that can provide services for the management of files by users on the network computer. The benefits derived from the user's cloud storage include data storage, data sharing, data synchronization via desktop pc or smart phone so that it can reduce the risk of data loss and ease of data sharing. Own Cloud is an open source designed to build cloud storage because it has many advantages, both in terms of ease of installation, configuration, and easier to use and having an application support for syncing with your computer or smart phone. The study was conducted based on the needs of a cloud storage system to enable employees of PT. Telkom Indonesia Kandatel perform range of data storage, data sharing and data backup, so that data storage will be centralized on a single server which is used as the storage. The system is expected to assist the work of employees in terms of sharing data through fast, precise, accurate, and efficient.